2016
DOI: 10.7314/apjcp.2016.17.3.993
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Epothilone A in Combination with the Antidiabetic Drugs Metformin and Sitagliptin in HepG2 Human Hepatocellular Cancer Cells: Role of Transcriptional Factors NF-κB and p53

Abstract: Type 2 diabetes mellitus patients are at increased risk of many forms of malignancies, especially of the pancreas, colon and hepatocellular cancer. Unfortunately, little is known of the possible interaction between antidiabetic drugs and anticancer agents. The present study investigates the influence of metformin (MET) and sitagliptin (SITA) on the in vitro anticancer activity of the microtubule depolymerization inhibitor agent epothilone A (EpoA). Hepatocellular liver carcinoma cell line (HepG2) viability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In some in vitro studies, it has also reported as an apoptotic agent on colon and pancreatic cancer cell lines. Remarkably, sitagliptin has shown antiproliferative and apoptogenic effects against the human hepatoma HEPG2 liver cancer cell lines …”
Section: Introductionmentioning
confidence: 99%
“…In some in vitro studies, it has also reported as an apoptotic agent on colon and pancreatic cancer cell lines. Remarkably, sitagliptin has shown antiproliferative and apoptogenic effects against the human hepatoma HEPG2 liver cancer cell lines …”
Section: Introductionmentioning
confidence: 99%
“…Its molecular mechanism includes activating NF-κB and increasing Bax, p53, and caspases-3, 8, and 9. Sliwinska et al found that metformin can accelerate the death of cancer cells induced by WP631 and reduce the dose of WP631, which may be related to a significant increase in the level of NF-κB in liver cancer cells (93). These authors also discovered that metformin enhanced the anti-hepatoma effect of tubulin depolymerization inhibitor epothilone A by enhancing its pro-apoptotic effect and increasing levels of NF-κB (94).…”
Section: Metformin With Cytotoxic Therapymentioning
confidence: 99%
“…7‐Aminoactinomycin D is a fluorescent dye that can also be used to detect viable/non‐viable cells (excluded by viable cells) by fluorescence microscopy and FCM (Zembruski, Stache, Haefeli, & Weiss, (Figure ). Rogalska, Sliwinska, Kasznicki, Drzewoski, and Marczak () have used 7‐aminoactinomycin D to monitor the effects of a drug combination (epothilone A, metformin and sitagliptin) on hepatocellular cancer (Hep G2) cell viability by FCM. The dyes in SYTOX family (blue, green, orange and red), TOTO and TO‐PRO are other fluorescence dyes (Figure ), which can penetrate only into dead cells (King, ).…”
Section: Cell Viability/cytotoxicity and Antiproliferative Assaysmentioning
confidence: 99%